2014
DOI: 10.1093/toxsci/kfu210
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Arsenic Exposure and the Epigenome: Identifying Sites of 5-methylcytosine Alterations that Predict Functional Changes in Gene Expression in Newborn Cord Blood and Subsequent Birth Outcomes

Abstract: Prenatal exposure to inorganic arsenic (iAs) is detrimental to the health of newborns and increases the risk of disease development later in life. Here we examined a subset of newborn cord blood leukocyte samples collected from subjects enrolled in the Biomarkers of Exposure to ARsenic (BEAR) pregnancy cohort in Gómez Palacio, Mexico, who were exposed to a range of drinking water arsenic concentrations (0.456-236 µg/l). Changes in iAs-associated DNA 5-methylcytosine methylation were assessed across 424,935 CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 32 publications
10
144
1
Order By: Relevance
“…While it may be intuitive that X-inactivation would likely present as a pattern of hypermethylation in females as compared with male placentas, prior research has shown that gene silencing on the X-chromosome is dependent on gene region and in some cases hypomethylation-associated silencing has been observed [49,52,53]. Taken together, these data support that the functional impact of methylation on X-chromosome inactivation exhibits positional dependencies, similar to those observed previously [54].…”
Section: Discussionsupporting
confidence: 84%
“…While it may be intuitive that X-inactivation would likely present as a pattern of hypermethylation in females as compared with male placentas, prior research has shown that gene silencing on the X-chromosome is dependent on gene region and in some cases hypomethylation-associated silencing has been observed [49,52,53]. Taken together, these data support that the functional impact of methylation on X-chromosome inactivation exhibits positional dependencies, similar to those observed previously [54].…”
Section: Discussionsupporting
confidence: 84%
“…2016), GSE62924 (Rojas et al 2015). Adult peripheral blood GSE74738 (Hanna et al 2016), GSE54399 (Montoya-Williams et al 2017.…”
Section: Auroc Stability Of the Fco Estimations And Synthetic Mixturmentioning
confidence: 99%
“…[21][22][23][24][25][26] However, significant DNA methylation disruption of unique loci along with enrichment of key regulatory CpG regions has been documented across different study populations. [22][23][24][25][26][27][28] Besides studies that examined cord and whole blood epigenome, only 2 studies to date have evaluated the association between arsenic exposure and CpG methylation of target tissue by evaluating DNA methylation in urothelial carcinoma samples and CpG methylation of exfoliated urothelial cells, respectively. 29,30 These studies found differentially methylated loci associated with arsenic exposure in key regulatory genes potentially involved in the development of arsenic-induced urothelial carcinoma.…”
Section: Introductionmentioning
confidence: 99%